Case report: anaplastic lymphoma kinase (ALK) rearranged adenocarcinoma with high level of microsatellite instability response to pembrolizumab - Shigeta, Naoko; Murakami, Shuji; Yokose, Tomoyuki; Miyagi, Yohei; Saito, Haruhiro (Frontiers in Oncology, 2023)
The presence of anaplastic lymphoma kinase (ALK) rearrangement is reported to be related to the lack of efficacy of immune checkpoint inhibitors (ICIs). High levels of microsatellite instability (MSI-high) are important biomarkers of ICIs, particularly in colorectal cancer. The therapeutic effect of ICIs for MSI-high NSCLC is uncertain because of the rarity of these tumors. Here we report a case of ALK rearranged NSCLC with MSI-high. A 48-year-old male was diagnosed with lung adenocarcinoma, cT4N3M1a, stage IVA with ALK rearrangement, high PD-L1 expression with a tumor proportion score (TPS) of 100%, and MSI-high. The patient was treated with alectinib as the first-line therapy but progressed at five months with left atrial invasion re-expansion. The patient discontinued alectinib and was switched to pembrolizumab monotherapy. After two months, left atrial invasion significantly decreased. The patient continued pembrolizumab for a year without noticeable adverse events, and tumor shrinkage persisted. This case supports the efficacy of ICIs for MSI-high NSCLC, even in the presence of ALK rearrangement.